Does higher education affect total factor productivity in Nepal? An exploration through the lens of ARDL bounds test - Dahal, Madhav Prasad (Economic Journal of Development Issues, 2015)
Education-centered human capital is one of the variables extensively used to model growth equations with the resurgence of growth theories in the 1980s primarily with the publication of Romer’s 1986 and Lucas’ 1988 seminal papers. Education contributes growth through its direct benefits to the individual and positive externality to the society. Theory claims that education enhances economic growth by working as an input of production and by being an agent of technological innovation, dissemination, and imitation. Previous empirical evidence on the effect of education on growth is mixed. This paper empirically examines the effect of higher education on total factor productivity in the aggregate level of the economy of Nepal employing time series data of the period 1975-2011 applying the ARDL method of cointegration. The findings are not encouraging on the issue.DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11869Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 76-102